Développement d’un jeu à scratch pour l’apprentissage du Texte de procédure en Français au niveau du lycée - Mahfudloh, Fatwa; Al Adawiyah, Aisyiah (Universitas Negeri Semarang, 2025)
Learning French, which is not an everyday language, is tricky for students to understand. The use of interesting French learning media for students is needed to present interactive learning and can simplify concepts that are difficult to understand. The development of learning media that researchers do is in the form of game development for French learning, especially to explain the structure of definite, indefinite, and possessive articles, as well as the conjugation of verbs of the Imperative form, based on the Basic Competencies of the material that needs to be achieved. This research aims to analyze the needs of teachers and students and describe how to develop Scratch game media for learning Procedure Text. The research and development method is used in this research. Development method, which is a research method used to produce specific products and test the effectiveness of these products. Researchers conducted five of the ten research stages: finding potential problems, data collection, product design, design validation, and design revision. The results of the respondents need learning materials that follow the basic skills of the material. Respondents also need learning materials that are consistent with speech act performances. Respondents are interested in technology-based learning materials. Scratch Game Development Process The game development process consists of seven steps, with the development result being a Scratch game for learning French procedure text at a high school level.